S. Holm, J. Lewis. Abortion: pro et contra / trans. from Engl. A. V. Nekhaev - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
The article provides a critical review of some of the most common arguments actively used in the abortion debate. Based on the notion of moral personhood, the main groups of such arguments (no full moral status, full moral status, and gradualism) are identified and characterized. Separate consideration is given to the right of pregnant women to abortion, the legal defense of the fetus’ right to life, and the practice of using the medical concept of viability in law.